Biokinetic Study of Microbial Decontamination of Oilfield Produced Water - B, Nwokoma Darlington; K, Dagde Kenneth; G, Akpa Jackson; Emmanuel, Ehirim (International Journal of Chemical and Process Engineering Research, 2022)
This work was aimed at identifying microbials and determining the biokinetic parameters for bio-decontamination of oilfield produced water. An extant physical treatment unit for produced water was re-engineered and retrofit with a discontinuous aerobic bioreactor (Bio-Unit) system. The Bio-Unit was operated in a fill-and-draw sequence and the rates of total organic carbon (TOC) removal and biomass growth were monitored. The isolated microbial strains were identified as Bacillus, Pseudomonas and Chryseobacterium spp. The biokinetic parameters of the bio-detoxification process were determined by fitting experimental data into the Monod Equation. The maximum specific substrate utilization rate (k_m), maximum specific growth rate (μ(m,h )), substrate half saturation coefficient (K(STOC )), yield (Y), and endogenous decay rate (b_h), were found to be 0.20 day-1, 0.31 day-1, 2.7 mg TOC/l, 1.6 mg MLSS/mg TOC, and 0.23 day-1, respectively. These values are within the range published in literatures for oilfield produced water, thus will suffice for designing, modeling and control of biological treatment systems, since biokinetic parameters for real oilfield produced water treatment using discontinuous biological configuration is scanty.